Evaluation of growth and biomass production of two strains of the Pleurotus spp., cultivated in an agar medium with different substrates - Coello-Loor, Carol Daniela (2017)
The rate of radial growth VCR (mm.h-1) and biomass production PB (g.g-1 of dry substrate) are techniques that help us to understand the degree of adaptation and development of mushrooms of the Pleurotus spp., genus in various substrates which could be applied in a solid medium fermentation. The synthetic culture medium used was potato dextrose agar (PDA), with a pH of 5.6 q 5.9 is ideal for fungal growth, as it has all the nutritional components and due to its slight acidity helps to inhibition the growth of bacteria, diluted in 4 different solutions prepared with the residual materials, with the purpose to observe the radial growth every 24 hours and the fungal biomass production of these lignocellulosic mushrooms during their period of incubation and adaptation which they could have in vitro. The species were Pleurotus sapidus and Pleurotus ostreatus IE8. the best VCR showed the treatments PoCaPDA and PoCaCmPDA and the better strain was the Pleurotus ostreatus in VCR and PB and the best culture medium was the CaPDA in both variables. Whereas in the production biomass treatments showed better results adaptation was the CaPDA Pleurotus sapidus (0.1727) and with CmPDA IE8 Pleurotus ostreatus (0.1722) CaPDA (0.1706) and PDA (0.1694).